The Dutch in America, 1609-1974, - De Jong, Gerald F. (Gerald Francis), 1921- (The Immigrant heritage of America series, 1975)
Traces the history of Dutch-Americans discussing why each wave of immigrants left Holland, where they settled, and their way of life in and contributions to their new country from colonial times to the present.